Barriers and possibilities for inland waterways in Sweden - The fifth mode of transportation - Arnholm, Maria; Leimalm, Madeleine (My University, 2015)
The society depends on transportation, both for goods and passengers. The future increase of transport volumes in combination with limited capacity of infrastructure can therefore become problematic. The shipping industry has an unexploited capacity and inland waterways can thus contribute to a sustainable transport industry. The purpose of the study was to investigate the possibility of using inland waterways for transports in Sweden. The thesis was built upon an exploratory study in order to identify the barriers and possibilities associated with traffic under the new directive (2006/87/EG) on inland waterways in Sweden. Furthermore, potential benefits that could arise and to whom they could be accrued was investigated. In order to gain understanding and retrieve information on the topic interviews were conducted with different stakeholders. The result of the interviews showed that barriers were related to high initial costs, difficulties in minimizing risk and transport buyers’ resistance to change transport mode. Furthermore it was concluded that the risk of the new directive only becoming a change in theory, and not in practice increased the longer it took for traffic to start. The possibilities were found in the fact that there is increasing transport demand that the current infrastructure cannot handle, thus new solutions have to be developed. Political decisions in terms of competition for different transport modes could also provide incentives for transport buyers to investigate other transport solutions. Further the result showed that the public welfare in, terms of lower socio-economic costs and less impact on the environment, would benefit from a shift to transporting cargo on inland waterways in Sweden. The study does not provide any comprehensive investigation of the new directive on inland waterways. Nor has any calculations regarding profits and costs been performed.
Keywords: Infrastrukturteknik; Building Futures; Transport; Infrastructure Engineering; Building Futures; Transport